2021
DOI: 10.1177/0886109920982094
|View full text |Cite
|
Sign up to set email alerts
|

Pandemics, Protests, and Feminist Politics of Resistance

Abstract: I am going to join all the ones I left at the shore. I am going home soon. I am going wherever I want to go, wherever the hell I want, somewhere, uncertain. I am going forward. I am going where you are going if where you are going is free. -Beltrán (2019, p. 148) In These Dangerous TimesFour years ago, February 2017, the then incoming editor-in-chief team, Drs. Rupaleem Bhuyan, Yoosun Park, and Stephanie Wahab, reflected that their initial enthusiasm to lead Affilia forward into its next chapter had been tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…We are certainly not the first editorial leadership team at Affilia to encounter and comment on difficult times. The last two editorial leadership teams also entered their tenure grappling with what it means to do critical feminism during moments of drastic political and social upheaval (Kim et al, 2021;Park et al, 2017). Our immediate predecessors raised alarms about social work educators losing their institutional positions due to their affiliations with abolitionist movements (Zelnick et al, 2023).…”
mentioning
confidence: 99%
“…We are certainly not the first editorial leadership team at Affilia to encounter and comment on difficult times. The last two editorial leadership teams also entered their tenure grappling with what it means to do critical feminism during moments of drastic political and social upheaval (Kim et al, 2021;Park et al, 2017). Our immediate predecessors raised alarms about social work educators losing their institutional positions due to their affiliations with abolitionist movements (Zelnick et al, 2023).…”
mentioning
confidence: 99%
“…Heightened vulnerabilities and an eroding capacity to withstand unrelenting changes and acceleration have occupied many pages of journals, including ours (Kim et al, 2021). Critical feminist research showed us how the pandemic disproportionately threatened the lives and well-being of Latinx immigrants (Cross & Gonzalez Benson, 2021), Latina immigrants (Cleaveland & Waslin, 2021), sex workers (Bromfield et al, 2021), intimate partner violence survivors (Heward-Belle et al, 2022), student mothers (LaBrenz et al, 2023), trafficking survivors (Namy et al, 2023), and anti-violence workers (Welch & Schwarz, 2023).…”
mentioning
confidence: 99%
“…One's vulnerability to hazardous conditions had already been shaped by race, gender, class, ability, sexuality, first language, and immigration status. Yet this historical moment seems to have intensified dynamics driven into overdrive by a knotty web of white supremacy, neoliberal capitalism, and patriarchy.Heightened vulnerabilities and an eroding capacity to withstand unrelenting changes and acceleration have occupied many pages of journals, including ours (Kim et al, 2021). Critical feminist research showed us how the pandemic disproportionately threatened the lives and well-being of Latinx immigrants (Cross & Gonzalez Benson, 2021), Latina immigrants (Cleaveland & Waslin, 2021), sex workers (Bromfield et al, 2021), intimate partner violence survivors (Heward-Belle et al, 2022), student mothers (LaBrenz et al, 2023), trafficking survivors (Namy et al, 2023, and anti-violence workers (Welch & Schwarz, 2023).…”
mentioning
confidence: 99%